2013
DOI: 10.1097/aln.0b013e31829996b6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of General Anesthetics on Substance P Release and c-Fos Expression in the Spinal Dorsal Horn

Abstract: Background We examined in vivo the effects of general anesthetics on evoked substance P release (primary afferent excitability) and c-Fos expression (neuronal activation) in superficial dorsal horn. Methods Rats received saline, propofol (100mg/kg), pentobarbital (50mg/kg), isoflurane (2 minimum alveolar concentration), nitrous oxide (66%) or fentanyl (30μg/kg). During anesthesia, rats received intraplantar 5% formalin (50μl) to left hindpaw. Ten min later, rats underwent transcardial perfusion with 4% paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…A related issue is that our use of pentobarbital anesthesia during the delivery of intradermal chemical stimuli might have reduced Fos expression. Indeed, pentobarbital was recently reported to reduce spinal Fos immunoreactivity elicited by formalin in rats (Takasusuki et al, ). However, we previously observed that pentobarbital at doses sufficient to block motor reflexes did not inhibit responses of dorsal horn neurons to noxious stimuli (Carstens and Campbell, ).…”
Section: Discussionmentioning
confidence: 99%
“…A related issue is that our use of pentobarbital anesthesia during the delivery of intradermal chemical stimuli might have reduced Fos expression. Indeed, pentobarbital was recently reported to reduce spinal Fos immunoreactivity elicited by formalin in rats (Takasusuki et al, ). However, we previously observed that pentobarbital at doses sufficient to block motor reflexes did not inhibit responses of dorsal horn neurons to noxious stimuli (Carstens and Campbell, ).…”
Section: Discussionmentioning
confidence: 99%
“…While no study has directly investigated the effect of isoflurane anesthesia on nociceptive spinal PERK activity, isoflurane is thought to have an inhibitory effect on neural activity [7][8][9][10]. Moreover, studies have indicated that injectable anesthetics such as propofol, fentanyl, and pentobarbital [11][12][13] as well as inhalational anesthetics such as nitrous oxide and isoflurane [14] reduced c-Fos expression in the spinal cord. While isoflurane reduces c-Fos expression, it does not alter primary afferent peptide release into the spinal cord as investigated by internalisation of the NK1 receptor for SP in the dorsal horn [13].…”
Section: General Anesthesia and Molecular Signalling In The Spinal Cordmentioning
confidence: 99%
“…Moreover, studies have indicated that injectable anesthetics such as propofol, fentanyl, and pentobarbital [11][12][13] as well as inhalational anesthetics such as nitrous oxide and isoflurane [14] reduced c-Fos expression in the spinal cord. While isoflurane reduces c-Fos expression, it does not alter primary afferent peptide release into the spinal cord as investigated by internalisation of the NK1 receptor for SP in the dorsal horn [13]. Takasusuki et al [13] suggested that while this result could implicate a role for non-peptidergic primary afferent activity accounting for the effects of general anesthesia, it is more likely that general anesthetics play a role in post-synaptic suppression of molecular nociceptive targets.…”
Section: General Anesthesia and Molecular Signalling In The Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic effects of drugs are determined by many factors, such as characteristics of drug, route of administration, and dosage form (Karande and Mitragotri 2009;Takasusuki et al 2013). In clinic practice, PLE and FC are easy to mix together before administration or in blood circulation, thereby possibly altering their dosage forms.…”
Section: Introductionmentioning
confidence: 99%